Different DNA Loidy Patterns for the Differentiation of Common Subtypes of Renal Tumors - Guorong Li; Michèle Cottier; Odile Sabido; Anne Gentil-Perret; Claude Lambert; Christian Genin; Jacques Tostain (Cellular Oncology)
Objectives: The common subtypes of renal tumors are conventional or clear cell carcinoma, papillary carcinoma, chromophobe carcinoma and oncocytoma. Each subtype has its distinct histogenesis and clinical evolution. DNA ploidy is viewed as a marker of gross genomic aberrations. The aim of this study is to evaluate the DNA ploidy in the common subtypes of renal tumors to increase our understanding of renal tumor biology and to broaden clinical application of DNA ploidy. Methods: 38 renal tumor samples (13 clear cell RCCs, 12 papillary RCCs, 7 chromophobe RCCs, and 6 oncocytomas) were studied. Five biopsies of different parts of each fresh tumor were subjected to a flow cytometric analysis of DNA ploidy. Results: All tumors except one papillary RCC generated interpretable DNA histograms. Flow cytometric analysis of oncocytomas showed the diploid pattern (29/30 frequencies) while the chromophobe RCC never showed the diploid pattern (0/55 frequencies) (p < 0.01). 3/7 chromopbobe RCCs possessed the hypodiploid stemline. The hypodiploid stemline appeared neither in conventional RCCs (0/63 frequencies) nor in papillary RCCs (0/50 frequencies). The diploid pattern was dominant in conventional and papillary RCCs. 10/13 (76.9%) of clear cell RCCs and 9/11 (81.8%) of papillary RCCs possessed a homogeneous DNA ploidy pattern while only 1/7 (14.3%) has a homogeneous DNA ploidy pattern. 6/7 chromophobe RCCs had multiple aneuploid stemlines. Conclusions: Flow cytometric analysis reveals that conventional and papillary RCCs are more homogeneous than chromophobe RCC. Each subtype of renal tumors possesses a specific DNA ploidy pattern. The analysis of DNA ploidy is useful for the differentiation of common subtypes of renal tumors in morphologically difficult cases.